In Search of a Workable Concept of “Undertaking” in Competition Law: ECJ’s Sumal v. Mercedes Benz - Díez Estella, Fernando (CUADERNOS DE DERECHO TRANSNACIONAL, 2022)
A decade after the approval of Directive 2014/104/EU, and its late transposition into Spanish law by Royal Decree Law 9/2017, actions for damages have flourished in the private enforcement of competition law, both in the EU and in Spain. In particular, the so-called “trucks cartel” has given rise to an unprecedented amount of litigation, in which the injured parties have overcome all kinds of obstacles, both substantive and procedural. Of these, undoubtedly one of the most complicated, due to the absence of a clear legal regime, is the alleged lack of passive legitimacy of the defendants. The CJEU ruling of 6 October 2021, which resolves this issue, addresses the analysis of the concept of “undertaking” in this regulatory field, establishing new rules that allow for a “downward” imputation of liability to subsidiaries for the anti-competitive conduct of their parent companies.
Keywords: Private enforcement; damages actions; liability; undertaking; economic single entity